Educational values and challenges of i-STEM project-based learning: A mixed-methods study with data-transformation design - Chang, Chi-Cheng; Chen, Yi-Kai (Frontiers in Psychology, 2022)
Integrated science, technology, engineering, and mathematics (STEM) embedding project-based learning (i-STEM PjBL) is still faced with challenges, and its educational values have not been revealed, which is what the study aimed to explore. Participants consisted of 48 freshmen from a senior high school, including 27 male students and 21 female students. The open-ended questionnaire and the interview for the students were administrated after the i-STEM PjBL. The qualitative data were converted into quantitative data counted by the occurrence frequencies of the codes. The results based on the integration and comparison of the open-ended questionnaire and interview outcomes showed that i-STEM PjBL provided students with positive educational values (including learning acquisition, performance, and perception), but there were also learning challenges in the process. Learning acquisition focused on the basic structure and components of a robot, principles of robot motion, hull structure, principles of sailboat navigation, and skills of designing and assembling sailboats. Learning performance referred that students were satisfied with their hands-on performances and confident of their abilities to perform better in similar disciplines, but did not learn well on programming. Learning perception indicated that students felt interested in i-STEM PjBL materials could acquire knowledge and skills from various fields, PjBL could be helpful to complete works, and principles could be helpful in practice, while programming design learning materials were not enough. Learning challenges indicated that students were unfamiliar with the usage of tools and hands-on operation, and they also felt challenged by programming. Students' feedback can be taken as references to modify and improve i-STEM PjBL and the materials in the future.